2020
DOI: 10.1038/s41598-020-69978-w
|View full text |Cite
|
Sign up to set email alerts
|

Immune outcomes of Zika virus infection in nonhuman primates

Abstract: Although the Zika virus (ZIKV) epidemic is subsiding, immune responses that are important for controlling acute infection have not been definitively characterized. Nonhuman primate (NHP) models were rapidly developed to understand the disease and to test vaccines, and these models have since provided an understanding of the immune responses that correlate with protection during natural infection and vaccination. Here, we infected a small group of male rhesus (Macaca mulatta) and cynomolgus (Macaca fascicularis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
3
8
0
Order By: Relevance
“…Several genes found to be upregulated in both the Lim 2020 and Schouest 2020 studies were also upregulated (FDR ≤ 0.05 and LFC ≥ 1.0) in our results, including IFI44, IFIT1, IFIT3, MX1, OAS1, and OASL ( Supplemental Figures 4–6 ). Finally, this study demonstrated that subclinical ZIKV infection can induce a protective immune response against re-exposure with an evolutionary distant ZIKV isolate, and that re-exposure to ZIKV induces an anamnestic immune response to the virus, even in the absence of detectable viremia, a finding that has also been reported in rhesus macaque models of ZIKV infection ( Osuna et al., 2016 ; Schouest et al., 2020 ; Schouest et al., 2021 ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Several genes found to be upregulated in both the Lim 2020 and Schouest 2020 studies were also upregulated (FDR ≤ 0.05 and LFC ≥ 1.0) in our results, including IFI44, IFIT1, IFIT3, MX1, OAS1, and OASL ( Supplemental Figures 4–6 ). Finally, this study demonstrated that subclinical ZIKV infection can induce a protective immune response against re-exposure with an evolutionary distant ZIKV isolate, and that re-exposure to ZIKV induces an anamnestic immune response to the virus, even in the absence of detectable viremia, a finding that has also been reported in rhesus macaque models of ZIKV infection ( Osuna et al., 2016 ; Schouest et al., 2020 ; Schouest et al., 2021 ).…”
Section: Discussionsupporting
confidence: 78%
“…Transcriptomic profiling of the baboon response to ZIKV infection revealed upregulation of genes associated with IFN alpha, beta, and gamma signaling and antiviral responses between days 0 and 3, then downregulation of the same sets of genes between days 3 and 15, a period when viral infection was effectively controlled. The upregulation of genes related to IFN signaling early in infection has been observed in other studies of ZIKV infection in whole blood of rhesus and cynomolgus macaques ( Schouest et al., 2020 ), as well as in human PBMCs in vitro ( Lim et al., 2020 ). Several genes found to be upregulated in both the Lim 2020 and Schouest 2020 studies were also upregulated (FDR ≤ 0.05 and LFC ≥ 1.0) in our results, including IFI44, IFIT1, IFIT3, MX1, OAS1, and OASL ( Supplemental Figures 4–6 ).…”
Section: Discussionsupporting
confidence: 63%
“…The tissues evaluated in this study were from healthy male rhesus ( Macaca mulatta ) and cynomolgus ( Macaca fascicularis ) macaques, born at their respective National Primate Research Centers ( Table 1 ). Archived reproductive tissues, including testes, epididymis, seminal vesicle, and prostate gland, from 51 ZIKV-infected and 8 age-matched, uninfected, male rhesus and cynomolgus macaques from past or ongoing collaborative research projects were kindly donated by the California (N = 35) [ 14 , 31 , 32 ], Tulane (N = 10) [ 69 ], Wisconsin (N = 6) [ 70 , 71 ], and Washington (N = 1 uninfected control rhesus macaque) NPRCs. These animals, aged 2 to 15 years old, were inoculated IV or SC with variable ZIKV strains and doses, humanely euthanized, and necropsied at 1 to 60 DPI.…”
Section: Methodsmentioning
confidence: 99%
“…All studies were approved by the appropriate Institutional Animal Care and Use Committees (IACUC). Archived reproductive tissues, including testes, epididymis, seminal vesicle, and prostate gland, from 51 ZIKV-infected and 8 age-matched, uninfected, male rhesus and cynomolgus macaques from past or ongoing collaborative research projects were kindly donated by the California (N = 35) (13,31,32), Tulane (N = 10) (70), Wisconsin (N = 6) (71, 72), and Washington (N = 1 uninfected control rhesus macaque) NPRCs. These animals, aged 2 to 15 years old, were inoculated IV or SC with variable ZIKV strains and doses, humanely euthanized, and necropsied at 1 to 60 DPI.…”
Section: Methodsmentioning
confidence: 99%